2023
DOI: 10.3390/ijms24076750
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effects of Insecticides on Aphids (Hemiptera: Aphididae): Resistance Mechanisms and Molecular Basis

Abstract: With the passage of time and indiscreet usage of insecticides on crops, aphids are becoming resistant to their effect. The different classes of insecticides, including organophosphates, carbamates, pyrethroids and neonicotinoids, have varied effects on insects. Furthermore, the molecular effects of these insecticides in aphids, including effects on the enzymatic machinery and gene mutation, are resulting in aphid resistance to the insecticides. In this review, we will discuss how aphids are affected by the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 146 publications
(163 reference statements)
0
7
0
Order By: Relevance
“…Unfortunately, due to the development of resistance, the relative ineffectiveness of organophosphates [19], pyrethroids [20], neonicotinoids [21], and carbamates [22] against aphids is often detected.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, due to the development of resistance, the relative ineffectiveness of organophosphates [19], pyrethroids [20], neonicotinoids [21], and carbamates [22] against aphids is often detected.…”
Section: Introductionmentioning
confidence: 99%
“…The GST and CarE could activate the detoxification system and alleviate the toxicity symptoms of insects as important detoxification enzymes. 40,41 The CarE participated energetically in the resistance of pyrethroid and organophosphorus insecticides in various pest species. 42−44 In this study, CarE gained enhanced detoxification ability because of compound 1, which further suggested that CarE was connected to the detoxification metabolism of 1.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticide resistance arises from a complex interplay of genetic, physiological, and environmental factors, including the rapid evolution of resistance mechanisms within aphid populations. Resistance mechanisms include insensitivity of the target site, metabolic detoxification, and behavioral adaptations, which together reduce the efficacy of chemical insecticides [7,8]. Recent studies have documented resistance to acetamiprid in several aphid species [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%